Effect of Air Velocity on Temperature Distribution in B40 and B100 Oil Burners - Rizqullah, Andre Rifqi; Saputro, Wiliandi; Saputro, Erwan (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
Dependence on fossil fuels has encouraged Indonesia to develop biodiesel, in line with the mandatory B40 policy. This study examines the effect of air velocity variations on the combustion performance of B40 (40% palm biodiesel and 60% diesel) and B100 (100% palm biodiesel) fuels. Experiments were conducted using an oil burner with air velocities of 20, 35, 45, 50, and 55 m/s. The flame temperature distribution was measured at distances of 150 mm, 300 mm, 450 mm, 600 mm, 750 mm, and 900 mm from the burner nozzle using a K-type thermocouple. The results showed that the flame temperature increased with air velocity, peaked at 45 m/s, and decreased at higher velocities. The B100 fuel produced a higher flame temperature than B40, with a maximum temperature of 1052°C. The decrease in temperature above 45 m/s is due to the cooling effect of the stronger airflow, which reduces combustion efficiency. The flame temperature also tends to decrease as the distance from the burner nozzle increases, reflecting the influence of turbulence and natural cooling on heat distribution. This study highlights the importance of controlling air velocity and measurement distance to optimize flame temperature and combustion efficiency in burner systems.